2019
DOI: 10.1002/ijc.32163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soluble carbonic anhydrase IX as predictive marker for efficacy of bevacizumab: A biomarker analysis from the geparquinto phase III neoadjuvant breast cancer trial

Abstract: We analyzed the predictive potential of pretreatment soluble carbonic anhydrase IX levels (sCAIX) for the efficacy of bevacizumab in the phase III neoadjuvant GeparQuinto trial. sCAIX was determined by enzyme‐linked immunosorbent assay (ELISA). Correlations between sCAIX and pathological complete response (pCR), disease‐free and overall survival (DFS, OS) were assessed with logistic and Cox proportional hazard regression models using bootstrapping for robust estimates and internal validation. 1,160 HER2‐negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…These biomarkers usually are not only expressed abnormally but are involved in the vital biological processes, including angiogenesis, differentiation, and growth [55]. Several predictive genomic biomarkers for bevacizumab have been identified in various indications, including pH-weighted amine chemical exchange saturation transfer echoplanar imaging [56], soluble carbonic anhydrase IX [57], and apelin/APLN [58], among others, while none has been prospectively validated yet [59]. The lack of any ability to identify patients who will benefit a priori, that is, the absence of a predictive biomarker, means that nearly every patient is treated with the antibody, in spite of not knowing which patients would be more likely to derive any benefit from it.…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers usually are not only expressed abnormally but are involved in the vital biological processes, including angiogenesis, differentiation, and growth [55]. Several predictive genomic biomarkers for bevacizumab have been identified in various indications, including pH-weighted amine chemical exchange saturation transfer echoplanar imaging [56], soluble carbonic anhydrase IX [57], and apelin/APLN [58], among others, while none has been prospectively validated yet [59]. The lack of any ability to identify patients who will benefit a priori, that is, the absence of a predictive biomarker, means that nearly every patient is treated with the antibody, in spite of not knowing which patients would be more likely to derive any benefit from it.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that genetic depletion of CAIX expression enhances the efficacy of bevacizumab in preclinical tumor models [29]. Furthermore, recent evaluation of soluble CAIX (sCAIX) induced by shedding in breast cancer patients treated with bevacizumab showed that sCAIX levels are predictive of therapeutic response to inhibition of angiogenesis [30]. However, the impact of targeting CAIX activity in combination with anti-angiogenic agents in a therapeutically relevant manner in breast cancer has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…CAIX can also be detected in tumour stroma, which is associated with poor prognosis [152]. As a consequence of ectodomain shedding and release in exosomes, CAIX can be detected in the body fluids of cancer patients, and this can be exploited for non-invasive screening or monitoring tumour response to therapy [153,154].…”
Section: Caix-clinical Translationmentioning
confidence: 99%